Deteksi Tingkat Kesehatan Keuangan Pt Pos Indonesia (Persero) Dengan Analisis Financial Distress - Rita Martini; Bobby Omega; Faridah Faridah (JURNAL RISET TERAPAN AKUNTANSI, 2020)
The analysis of bankruptcy risk using the method of Z-Score model Altman and Method Zmijewski (X-Score) aimed at determining the potential of bankruptcy at PT Pos Indonesia (Persero). Authors using secondary data include financial statements in 2014-2018, the company's history and the company's organizational structure. After the authors do calculations and analyses based on the method of Z-Score model Altman can be concluded that PT Pos Indonesia (Persero) is in a hazardous zone with the rating standard Z-Score < 1, 81 and based on calculations and analyses based on the method Zmijewski obtained that the value of the calculation result of the company in the year 2015 and 2016 indicates that the company is in the financial category distress because the value of X > 0 and in 2014, 2017 and 2018 in the category of nonfinancial distress.